Islamic Perspectives on the Question of History - Taha Jabir Al-'Alwani (International Institute of Islamic Thought, 1990)
Here at the outset, I should like to emphasize to my esteemed brothers and sisters that my knowledge of the study of history as element in the contemporary social sciences is very limited. Yet, by making this admission before you, perhaps I can make my excuses early for aslung too many questions, or for putting into words some of the major difficulties I have with this subject, and perhaps others have as well. Indeed, when we think of this important branch of knowledge a number of issues immediately come to mind. Perhaps among the most significant of these issues are the following: 1. What is the overall meaning of human history? What is its legithate subject? What are its contents? 2. Is there any way to connect, historically, the remarkable abundance of diverse and multiplex events experienced by humankind all cwer the globe? Haw are trends to be explained, in the light of logical, rational relationships that transcend the time and place of their occurrence, as well as the special limitations of peoples and societies? And, is there any way to translate what is gained from these events into laws and principles that may be applied to the present, or that may afford a glimpse into the future, or that may explain the meaning of good and evil? 3. Is it reasonable for us to think of human history as a logical, ordered process by means of which humankind proceeds from its beginnig to its end? If so, was the master plan conceived from without? Or does it come about from history itself? Furthermore, is all this beyond the mch of man himself ...